Analisis dan Perancangan Sistem Informasi Reservasi Tour and Travel Menggunakan Metode OOAD Pada Warok Tour and Travel - Toufan Khoirin Nasikhin; Widhy Hayuhardhika Nugraha Putra; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Information system has important requirement in the business. The technology makes the importance of accurate and fast information needs to support the activities and operational activities of a company. With the tour and travel reservation information system, customers can make online travel booking transactions. System is designed using the Objected Oriented method. In this method need analysis by interview with the owner of the Warok Tour and Travel company to determine the functional and non-functional requirement. In design, UML are used is Use Case Diagrams, Activity Diagrams, Class Diagrams, Sequence Diagrams, and Physical Data Models. Then the user interface design is made to provide an overview of the system. The design testing process is carried out using the traceability method and review interface to 2 user. In requirement analysis process resulted the identification of users is 2 users, 10 functional requirements and 4 non-functional requirements. In the component design it produces a use case diagram with 8 use cases. In the design process produces 8 activity diagrams, 13 sequence diagrams, class diagrams, physical data models, 8 interface design sketches, and 15 prototype designs. Design testing is carried out using traceability methods and user prototype reviews, all of them are valid.